Strategi Pengelolaan Asrama Haji Embarkasi Bekasi Dalam Meningkatkan Nilai Guna - Imanda, Mutiara Hanifa; Aziz, Rohmanur (Mabrur: Academic Journal of Hajj and Umra, 2025)
The purpose of this research is to determine the formulation of management strategies to increase use value in the Implementation Unit, implementation of management strategies to increase use value, and evaluation of management strategies to increase use value in the Bekasi Embarkation Hajj Dormitory Technical Implementation Unit. This research shows the results that, the strategy for managing the Bekasi Hajj Embarkation UPT in increasing the Use Value consists of three stages. First, Formulation of management strategies to increase value select specific strategies to achieve goals. Second, implementation of management strategies to increase use value includes division of work tasks; Marketing and Budget; Organizational performance. Third, evaluate management strategies to increase the use value of the Bekasi Hajj Embarkation Dormitory Technical Implementation Unit.